Insulin pump breakdown and infusion set failure in Italian children with type 1 diabetes: A 1‐year prospective observational study with suggestions to minimize clinical impact. Issue 11 (18th July 2018) - Rabbone, Ivana; Minuto, Nicola; Toni, Sonia; Lombardo, Fortunato; Iafusco, Dario; Marigliano, Marco; Schiaffini, Riccardo; Maltoni, Giulio; Frongia, Anna P.; Scardapane, Marco; Nicolucci, Antonio; Cherubini, Valentino; et al.
Abstract : Aim: To evaluate the incidence of insulin pump and infusion set failures in a cohort of children and adolescents with type 1 diabetes during a 1‐year follow‐up. Materials and Methods: Insulin pump breakdown and infusion set failures were prospectively registered in a cohort of 1046 children and adolescents from 25 tertiary pediatric diabetes centres (50% male, mean age 12.2 ± 4.1 years), with type 1 diabetes from the age of 6.7 ± 3.6 years, and using an insulin pump from the age of 3.3 ± 2.2 years. Results: An average rate of 4.5 failures/person‐year was registered; the incidences (events per person‐year) for each failure were 8.4 for hyperglycaemia episodes solved with infusion set change, 7 for bubbles, 2.8 for kinking, 2.4 for bleeding, 2 for set dislodge, 2 for pump blockage, 1.9 for tunnelling, 1.8 for lipohypertrophy, and 0.3 for infection. At multivariate analysis significant association between HbA1c and lipohypertrophy ( P < 0.0028) was shown. Analysis by age group (<6, 6–11, >11 years) showed a higher frequency of bubbles, hyperglycaemia episodes and lipohypertrophy in preschoolers; tunnelling and pump blockage were more frequent in adolescents. Aspart was associated with a lower risk of bubbles and hyperglycaemia whereas glulisine was associated with a higher risk of lipohypertrophy and pump blockage. The usage of oblique cannula was associated with a low risk of all failures except infections. Conclusions: This prospective 1‐year study on a large cohort of Italian children and adolescents with type 1 diabetes using insulin pump therapy showed a low total failure rate, highlighting the importance of continuous education to reduce failures. Lipohypertrophy was the only issue associated with a worsening of metabolic control.